Classification of broncholiths and clinical outcomes. Issue 4 (25th April 2013) - Lim, So Y.; Lee, Kyung J.; Jeon, Kyeongman; Koh, Won‐Jung; Suh, Gee Y.; Chung, Man P.; Kim, Hojoong; Kwon, O Jung; Um, Sang‐Won
Abstract Background and objective We evaluated effective treatments of broncholithiasis based on its radiographical and bronchoscopic features. Methods This retrospective study conducted at Samsung Medical Center, Korea enrolled patients who were suspected of having broncholithiasis based on chest computed tomography (CT). The broncholiths were classified as intraluminal, mixed (both intraluminal and extraluminal) and extraluminal based on chest CT and bronchoscopic findings. Results The study enrolled 46 patients between 1995 and 2009. Symptoms included cough (n = 21, 45.7%), hemoptysis (n = 19, 41.3%) and purulent sputum (n = 11, 23.9%). Cough was more common in intraluminal boncholiths than in other type of broncholiths (P = 0.03). Based on chest CT, there were 15 (32.6%) intraluminal, 15 (32.6%) mixed and 16 (34.8%) extraluminal broncholiths. All 15 intraluminal broncholiths were removed completely via flexible (n = 2) or rigid (n = 13) bronchoscopy. For the 15 mixed broncholiths, seven (46.7%) bronchoscopic interventions were performed, but complete removal of the broncholiths was not accomplished. Six (40%) mixed and four (25%) extraluminal broncholiths were treated by surgical resection for symptom control. None of the patients who underwent surgical resection suffered morbidity or postoperative mortality. Conclusions The treatment of broncholithiasis should be based on chest CT and bronchoscopic findings. Intraluminal broncholiths can be removed via bronchoscopy, while surgery should be considered for symptomatic mixed or extraluminal broncholiths.